Volitional social interaction prevents drug addiction in rat models. (November 2018) - Venniro, Marco; Zhang, Michelle; Caprioli, Daniele; Hoots, Jennifer; Golden, Sam; Heins, Conor; Morales, Marisela; Epstein, David; Shaham, Yavin
Abstract Addiction treatment has not been appreciably improved by neuroscientific research. One problem is that mechanistic studies using rodent models do not incorporate volitional social factors, which play a critical role in human addiction. Here, using rats, we introduce an operant model of choice between drugs and social interaction. Independent of sex, drug class, drug dose, training conditions, abstinence duration, social housing, or addiction score in Diagnostic & Statistical Manual IV-based and intermittent access models, operant social reward prevented drug self-administration. This protection was lessened by delay or punishment of the social reward but neither measure was correlated with the addiction score. Social-choice-induced abstinence also prevented incubation of methamphetamine craving. This protective effect was associated with activation of central amygdala PKCδ-expressing inhibitory neurons and inhibition of anterior insular cortex activity. These findings highlight the need for incorporating social factors into neuroscience-based addiction research and support the wider implantation of socially based addiction treatments. Venniro et al. report that drug-addicted rats reliably choose contact with another rat over drugs, even when group-housed between tests. They also do not show the increase in drug craving that normally occurs during forced abstinence.